Application of fourier transform infrared vibrational spectroscopy in identifying early biochemical changes in lipid profiles of individuals undergoing Roux-en-y gastric bypass - Amanda Motta de Bortoli; Márcia Helena Cassago Nascimento; Blanca Elena Guerrero Daboin; Beatriz Bobbio de Brito; Luiza Recla Pessotti; Paulo Roberto Filgueiras; Andressa Bolsoni Lopes; Valerio Garrone Barauna; Fabiano Kenji Haraguchi (BMC Surgery)
Abstract Background Fourier transform infrared spectroscopy (FTIR) is an analytical technique increasingly applied in biological analysis. This study investigates the application of FTIR to identify early biochemical changes, particularly in lipid profiles, in individuals undergoing Roux-en-Y gastric bypass (RYGB). Methods An observational study involving patients from a university hospital’s Bariatric and Metabolic Surgery Program, with evaluations performed before (T0) and two months after (T1) RYGB. Biochemical parameters, anthropometric data, and body composition were assessed. FTIR spectra were pre-processed and analyzed using Principal Component Analysis and Partial Least Squares Discriminant Analysis. The normality of the data was evaluated using the Kolmogorov-Smirnov test, followed by paired T-tests or Wilcoxon tests as appropriate. Spearman correlation analysis of spectral information with biochemical parameters was also performed. A significance level of p < 0.05 was set for all tests. The university hospital’s Research Ethics Committee approved the study (protocol CAAE 59075722.7.0000.5071). Results The study evaluated 29 individuals (86.2% female) with a mean age of 41.2 ± 7.8 years. Significant differences were observed in anthropometric parameters and body composition (p < 0.001). Additionally, early improvements in the lipid profile were noted, with significant decreases in triglycerides, total cholesterol, and LDL cholesterol (p < 0.05) just two months post-surgery. FTIR identified correlations between biochemical parameters and specific spectral regions at T0 and T1. Notably, serum triglycerides showed a significant correlation with the lipid-specific spectral region (1796–1685 cm− 1) at both time points (p < 0.05). Conclusion FTIR can effectively monitor biochemical changes in RYGB surgery patients. The spectral range associated with lipid functional groups (1796 –1675 cm⁻¹) showed a significant relationship with serum triglyceride levels before and after RYGB. Additionally, various biochemical parameters exhibited strong correlations with other spectral regions, implying that the serum spectral profile can indicate biochemical variations at different post-surgery stages. Trial registration Brazilian Registry of Clinical Trials (Rebec), September 5, 2022, protocol RBR-26chs2g.